2019
DOI: 10.3389/fmicb.2019.02923
|View full text |Cite
|
Sign up to set email alerts
|

Cyprinid Herpesvirus 2 miR-C12 Attenuates Virus-Mediated Apoptosis and Promotes Virus Propagation by Targeting Caspase 8

Abstract: DNA viruses, most notably members of the herpesvirus family, generally encode miRNAs to mediate both virus and host genes expression. We previously demonstrated that Cyprinid herpesvirus 2 (CyHV-2) encodes 17 miRNAs that are involved in innate immune signaling pathways. In this study, the function of CyHV-2-encoded miRNA was further investigated in GiCF cells. We found that miR-C4 promoted CyHV-2-induced apoptosis, while miR-C12 decreased CyHV-2-induced apoptosis. miR-C12 targeted to 3′ UTR sequence of caspase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
(48 reference statements)
0
11
0
Order By: Relevance
“…Lu et al . (2019) reported that CyHV‐2 miR‐C12 suppresses virus‐induced apoptosis and promotes virus replication by targeting caspase 8 and over‐expression of miR‐C12 reduces the expression of caspase 8 and inhibits CyHV‐2 induced apoptosis. Fan et al .…”
Section: Impact Of Infection On Fishmentioning
confidence: 99%
See 3 more Smart Citations
“…Lu et al . (2019) reported that CyHV‐2 miR‐C12 suppresses virus‐induced apoptosis and promotes virus replication by targeting caspase 8 and over‐expression of miR‐C12 reduces the expression of caspase 8 and inhibits CyHV‐2 induced apoptosis. Fan et al .…”
Section: Impact Of Infection On Fishmentioning
confidence: 99%
“…Very recently, the same team found that, out of the 17 viral miRNAs, CyHV‐2 miR‐C12 is the important suppressor of CyHV‐2‐induced apoptosis of host cells by down regulating caspase 8 expression, promoting viral latency and propagation (Lu et al . 2019). In brief, evidences suggest that CyHV‐2, may become latent and/or persistent in surviving fish after acute infection.…”
Section: Impact Of Infection On Fishmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, some viral miR-NAs encoded by CyHV-2 have been identified in kidney tissue from CyHV-2-infected crucian carp. Among them, miR-C12 attenuated virus-mediated apoptosis and promoted virus replication in host cells by targeting Caspase 8 (Lu et al, 2017(Lu et al, , 2018(Lu et al, , 2019. But research on CyHV-2 virus is still limited.…”
mentioning
confidence: 99%